The role of Public Diplomacy in foreign policy of Turkey towards Georgia - L. M. Aleksanyan (Проблемы постсоветского пространства)
The article is devoted to the analysis of the role of public diplomacy in Turkey’s foreign policy towards Georgia. Special attention is paid to the processes of conceptualization and institutionalization of Turkish public diplomacy. The author examines its goals and objectives. The attention is focuses on main institutions of Turkish public diplomacy, which implement cultural, humanitarian and educational projects in Georgia. The phenomenon of Turkish TV series are analyzed as one of the tools for creating an attractive image of the country in Georgian society. The level of effectiveness of Turkish public diplomacy towards Georgia is determined. In the context of this assessment, the image of Turkey is studied, as well as its ability to influence the political decisions of Georgia. General conclusions are made in regard to the Turkey foreign policy towards Georgia for the effectiveness of vector, its shortcomings are pointed out and further progress is noted.